Learning situation for the trigonometric Fourier series from a socio-epistemological standpoint - Farfán Márquez, Rosa María (2019)
This article aims at showing a didactic proposal that favours the signification of the Trigonometric Fourier Series through a learning situation, based on the Socio-epistemological Theory of Mathematics Education, on research where this knowledge has been problematized. The Fourier Trigonometric Series is a complex topic for learning at a higher level, where the process is usually mechanised without fully understanding its operation and characteristics. We want to verify that with activities that support the relationship between algebra and geometry, making use of GeoGebra – dynamic geometry software – as a control variable, the series and its convergence can be signified using a physical-geometric context.